2016
DOI: 10.1039/c6ee00700g
|View full text |Cite
|
Sign up to set email alerts
|

Li–O2 cells with LiBr as an electrolyte and a redox mediator

Abstract: Improved efficiency and cyclability of cells containing LiBr demonstrate that the appropriate choice of electrolyte solution is the key to a successful Li–O2 battery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
247
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 240 publications
(264 citation statements)
references
References 34 publications
15
247
0
2
Order By: Relevance
“…The large specific surface area of 2D materials is favorable to be full contact and infiltration with the electrolyte and oxygen. 50 The oxygen vacancies in the interior facilitate the electron and Li + conductivity as well as accelerate OER process as active sites binding to O2 and Li2O2. 51 The nanosheets have more Co 3+ on the surface and more Co 2+ in the inner.…”
Section: Resultsmentioning
confidence: 99%
“…The large specific surface area of 2D materials is favorable to be full contact and infiltration with the electrolyte and oxygen. 50 The oxygen vacancies in the interior facilitate the electron and Li + conductivity as well as accelerate OER process as active sites binding to O2 and Li2O2. 51 The nanosheets have more Co 3+ on the surface and more Co 2+ in the inner.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, sustainable charge redox mediators could accelerate the decomposition of insulating products by moving into the cathode electrode and facilitating the transport of electrons between the insulating products and the cathode electrode during charging. Many charge redox mediators have been reported, such as lithium iodide (LiI), [151,152] lithium bromide (LiBr), [148,153] tetrathiafulvalene (TTF), [82] tris [4-(diethylamino)phenyl]amine (TDPA), [154] 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO), [155,156] phthalocyanine (FePc), [157] and heme molecules. [158] Taking the iodide (I -) ion as an example, it could be oxidized to I 3 − or I 2 on the surface of the electrode during charging and then react with Li 2 O 2 to form Li + and O 2 gas with the regeneration of I − ions.…”
Section: Charge Redox Mediatormentioning
confidence: 99%
“…However, solid catalysts such as noble metals have been reported to promote not only the reversible decomposition of Li 2 O 2 but also electrolyte decomposition. [10,11] Alternatively, liquid catalysts, called redox mediators (RMs), [10][11][12][13][14][15][16] have been added to the electrolyte as electron-hole transfer agents to promote reversible Li 2 O 2 formation/ decomposition. [10,11] Alternatively, liquid catalysts, called redox mediators (RMs), [10][11][12][13][14][15][16] have been added to the electrolyte as electron-hole transfer agents to promote reversible Li 2 O 2 formation/ decomposition.…”
mentioning
confidence: 99%
“…However, it has recently been reported that RMs can be deactivated during cycling through chemical reduction at the Li metal electrode (self-discharge of the electrochemically oxidized RM) and attack by oxygen species at the cathode. [15,42] A graphene-polydopamine composite was developed as a protective layer and was uniformly coated onto the Li metal electrode to suppress undesired reactions with LiBr in the electrolyte, as well as with oxygen and moisture. [20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] However, reported Li protection materials and Li-protective layers mainly consist of polymers, which have insufficient stiffness to suppress the growth of Li dendrites.…”
mentioning
confidence: 99%